Pelatihan Penghitungan dan Pengisian SPT PPh Pasal 21/26 di Pondok Pesantren Muhammadiyah Ahmad Dahlan - Husni Mubarok; Ery Suryanti; Hendra Lesmana; Bernadette Cahya Putri Utami (Politeknik Negeri Cilacap, 2022)
Community Service as a unit of Higher Education Tri Dharma College aims to improve the standard of living of the community around the campus, the interests of Islamic boarding school students increase the scientific repertoire of Calculation and Filing of SPT PPh Pasal 21/26 which is accurate and correct as a debriefing to face work readiness in the industrial business world. The descriptive analysis method is a mixture of qualitative and quantitative to describe the characteristics of respondents and the tendency of students towards training from primary and secondary data. The training for calculating and filling PPh Pasal 21 is very unique, interestingly, the students are very enthusiastic about learning taxation and can add to the scientific treasures with the results of the initial test and final test being very unique from 57 respondents, interestingly from 37,34 the predicate changed to 86,97 the predicate was good.